Isotretinoin: action on mice tooth germs and palate - Eleny Balducci Roslindo; Vanessa Camila da Silva; Alessandra Rezende Peris; Karina Gonzales Silvério (Universidade Estadual de Campinas, 2015)
Vitamin A and its derivates, acid retinoic, tretinoin and isotretinoin, are currently used in dermatological treatments. The administration of high doses of this vitamin provokes malformation in the following systems: central nervous, cardiovascular, skeletal, brain and face. This study compares the tooth germs of the first maxillary and mandibular molars and the palate of fetal mice submitted to isotretinoin during organogenesis. Twelve 60-day-old female Mus musculus were divided into two groups on the 7th day of pregnancy: treated group - 2 mg isotretinoin per kg body wight, dissolved in vegetable oil, was administered orally from the 7th to the 13th day of pregnancy; control group - vegetable oil in an equivalent volume was administered orally for the same period. On the 16th day of pregnancy, the females were sacrificed, the fetuses were removed and their heads were amputted. After standard laboratory procedures, 6-mm-thick serial sections were stained with hematoxylin and eosin for light microscopy examination. The results showed that the control group had closed palates with no traces of epithelial cells and two fetuses of treated group had insufficient development in the lateral palate processes, having lack of fusion in the midline. The first molar germs of the isotretinoin-treated animals showed delayed development compared to the control animals. In conclusion, isotretinoin was shown to be toxic causing retardation of tooth germs and palate development.